Sepsis and Immunosenescence in the Elderly Patient: A Review - Martín, Silvia; Pérez, Alba; Aldecoa, Cesar (Frontiers in Medicine, 2017)
Sepsis is a prevalent, serious medical condition with substantial mortality and a significant consumption of health-care resources. Its incidence has increased around 9% annually in general population over the last years and specially in aged patients group. Several risk factors such as comorbidities, preadmission status, malnutrition, frailty, and an impared function in the immune system called immunosenescence are involved in the higher predisposition to sepsis in the elderly patients. Immunosenescence status consists in a functional impairment in both cell-mediated immunity and humoral immune responses and increases not only the risk for develop sepsis but also lead to more severe presentation of infection and may be is also related with a higher mortality. There is a also a concern about to admit patients in the intensive care units taking into account that the outcome of elderly patients is poorer compared to younger people. Nevertheless, the management of septic elderly patients does not differ substantially from younger people. In addition, the quality of life in septic elderly survivors is also lower than in younger people. But age, as alone factor, should not be used to determine treatment options because the poorer outcomes is thought to be due to the increased comorbidities and frailty in this group of patients.